The bomb [videorecording (DVD)] - DeNooyer, Rushmore (PBS, 2015)
This is the story of the most powerful and destructive device ever invented. With newly restored footage, go behind the scenes of the first atomic bomb, revealing how it was developed and how it changed the planet. Examine the choices society has made since 1945, and continues to make, to live with an invention that could destroy the planet.